Effects of Rubus fruticosus and Juniperus oxycedrus derivatives on culturability and viability of Listeria monocytogenes - Federica Barbieri; Chiara Montanari; Vida Šimat; Danijela Skroza; Martina Čagalj; Sonja Smole-Možina; Daniela Bassi; Fausto Gardini; Giulia Tabanelli (Scientific Reports, 2022)
Abstract The consumers’ demand for safe foods without chemical additives increased the research for green solutions, based on natural antimicrobials. Plants can be an important source of bioactive compounds able to prevent the development of foodborne pathogens and spoilage microflora. This paper aimed to characterize phenolic extracts (PEs) and essential oils (EOs) obtained from Mediterranean Rubus fruticosus leaves and Juniperus oxycedrus needles and to evaluate their antimicrobial effects against Listeria monocytogenes Scott A. The growth dynamics with sub-lethal concentrations of plant derivatives were modeled and flow cytometry was used to better evidence the effect on cell viability and culturability. The results showed that these plant derivatives affected the growth of L. monocytogenes, increasing lag phase (about 40 h in the presence of PEs vs. 8 h in the control) and decreasing the final cell load of at least 1 log cycle with respect to the control. R. fruticosus EO was the most effective, determining an initial decrease of cell counts of about 6 log cycles, followed by a restart of growth after 10 h, with rate similar to the control (0.08 with R. fruticosus EO vs. 0.09 ((log CFU/ml)/h in the control) but significantly lower final cell load (7.33 vs. 8.92 log CFU/ml). According to flow cytometry, only R. fruticosus EO induced a relevant increase of dead cells, while the other plant derivatives determined different extent of sub-lethal cell injury. The discrepancy observed in some cases between viability and culturability could indicate the presence of cells not able to grow in culture media, whose fate needs to be further investigated to assess their potential recovery, thus bringing to an overestimation of the antimicrobial effect of these substances. This research contributed to increase the knowledge of these underused raw materials such as blackberry leaves and juniper needles that can be exploited in food and other industries.